1985
DOI: 10.1161/01.cir.71.5.889
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous assessment of left ventricular systolic and diastolic dysfunction during pacing-induced ischemia.

Abstract: Both systolic and diastolic dysfunction have been described during pacing-induced ischemia, but the temporal sequence of systolic and diastolic impairment has not been established. Accordingly, 22 patients with coronary artery disease were paced at increasing heart rates and studied with simultaneous hemodynamic monitoring, electrocardiographic recording, and radionuclide ventriculography. In addition, with synchronized left ventricular pressure tracings and radionuclide volume curves, three sequential pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(77 citation statements)
references
References 38 publications
4
71
1
1
Order By: Relevance
“…Diastolic dysfunction is a feature of HCM and explained by increased chamber stiffness and impaired LV relaxation, while systolic function usually remains normal to supranormal. 5 Diastolic dysfunction often precedes systolic dysfunction 30 and heart failure dominates the clinical status in the progressive stage. HCM patients with heart failure have dilated ventricular cavities and commonly exhibit transmural scarring in the ventricular septum.…”
Section: Discussionmentioning
confidence: 99%
“…Diastolic dysfunction is a feature of HCM and explained by increased chamber stiffness and impaired LV relaxation, while systolic function usually remains normal to supranormal. 5 Diastolic dysfunction often precedes systolic dysfunction 30 and heart failure dominates the clinical status in the progressive stage. HCM patients with heart failure have dilated ventricular cavities and commonly exhibit transmural scarring in the ventricular septum.…”
Section: Discussionmentioning
confidence: 99%
“…This, however, underscores that in univentricular hearts, HR crit is significantly shifted to the left. At the ultrastructural level, studies on transgenic models of phospholamban overexpression (21) have elegantly shown that when the HR crit is shifted to the left, it indicates impaired Ca 2Ï© uptake by the SR. At the physiologic level, the decrease in HR crit may represent inadequate myocardial perfusion at faster HRs (29).…”
Section: Effects On Diastolic Propertiesmentioning
confidence: 99%
“…the inotropic state, suction effects in the ventricle,7,8 and the heart rate. 9 These factors are interrelated and can affect filling dynamics in both early and late diastole. Under resting conditions, increasing heart rate by atrial pacing augments early diastolic filling and shifts the LV diastolic pressure-volume relation downward.9 During exercise, increased heart rate has an important role in increasing the cardiac output.10"'1 Recent studies from this laboratory show that exercise in normal conscious dogs also markedly enhances early diastolic LV filling with a downward shift of the early portion of the LV diastolic pressure-volume curve, the average value of the pressure nadir being negative despite a marked increase in diastolic filling and considerable reduction of the filling time compared with resting conditions."…”
mentioning
confidence: 99%